Wzajemny wizerunek sąsiadów. Metodologiczna propozycja badań kulturoznawczych - Rosjanie w oczach Polaków - Boroch, Robert (Acta Polono-Ruthenica, 2006)
The research of cultural transmission between Russia and Poland has been carried out since 1990 in wide range of contexts as a) sociological; b) psychological; c) political; d) cultural anthropology; e) religiousness.